Off-pump ascending aorta or aortic arch to descending aorta bypass with a pericardial roll for the treatment of critically ill infants with interrupted aortic arch - Oztas, Didem M.; Meric, Mert; Beyaz, Metin O.; Coban, Senay; Sari, Gizem; Yildiz, Yahya; Ulukan, Mustafa O.; Unal, Orcun; Rodoplu, Orhan; Sungur, Zerrin; YOZGAT, Yılmaz; YOZGAT, YILMAZ; et al. (My University, 2020)
Aim: Standard surgical treatment of the interrupted aortic arch with the use of cardiopulmonary bypass is risky especially in critically ill babies. In this manuscript, we present the results of off-pump pericardial roll bypass for the treatment of aortic interruption. Material and methods: The technique was applied in nine critically ill infants between July 2011 and December 2019. Data were reviewed retrospectively. There were four girls and five boys. The types of the interruption were type B in six cases and type A in three babies. Additional cardiovascular anomalies were ventricular septal defect in all, atrial septal defect or patent foramen ovale in all, single-ventricle pathologies in two and bicuspid aortic valve in three cases. All the patients were in critical situations such as intubated, having symptoms of infection, congestive heart failure or ischaemia and malperfusion leading visceral organ dysfunction. Results: All patients underwent off-pump ascending aorta or aortic arch to descending aorta bypass with a pericardial roll. Post-operative early mortality occurred in one patient with severe mitral regurgitation due to cardio-septic shock. One patient who had single-ventricle pathology underwent bidirectional Glenn and was lost on the post-operative 26th day due to sepsis 2 years after operation. Two patients presented with dilatation of the pericardial tube 18 and 24 months after the operations and one underwent reconstruction of the neo-arch. The remaining patients are asymptomatic, active and within normal limits of body and mental growth. Conclusion: Treatment of interrupted aortic arch with a bypass with an autologous pericardial roll treated with gluteraldehyde without cardiopulmonary bypass seems a safe and reliable technique especially for the treatment of critically ill infants.